(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2008)
This report is the record of the Workshop proceedings, which includes summaries both the presentations made by the participants from the Central Asian countries and those made by resource persons from the United Kingdom, Turkey and FAO.
Keywords: Fisheries,Irrigation systems,Thuỷ sản,Hệ thống thuỷ lợi; Asia,Châu Á